Self-Reliance Profile of Primary Students in West Java Indonesia - Mulyasari, Effy; Ali, Mohammad; Sukirman, Dadang (Mimbar Sekolah Dasar, 2023)
This study aims to describe the profile of primary students' self-reliance in West Java Indonesia. This initial study is needed in order to provide a portrait of the primary student self-reliance, especially students’ independent living skills. This will be very useful for each student to be ready to face their future life. A survey is used to get the data needed. There were 366 teachers represented from 20 counties and 10 cities in West Java. They teach 92,1% at public schools 7,9% at private schools. By using Winstep for Windows and reliability 0,96 by the Rasch Model, the Mean Person Measure value of 0.27 logit shows the tendency of respondents who answer more to agree with statements. The tendency for student self-reliance is in the moderate category, which means students are able to 1) identify, explore, and analyze problems, 2) take the initiative to be self-reliant, and 3) be relied on by others. Therefore, the recommendation is to develop a micro curriculum model to support students’ self-reliance on finishing tasks or solving problems in independent living skills besides supporting those three self-reliance competence aspects at the primary school level in West Java